Sex Differences Between Female and Male Newborn Piglets During Asphyxia, Resuscitation, and Recovery - La Garde, Ramin P.; Cheung, Po-Yin; Yaskina, Maryna; Lee, Tze-Fun; O'Reilly, Megan; Schmölzer, Georg M. (Frontiers in Pediatrics, 2019)
Background Male and female newborns have differences in their fetal development, fetal-to-neonatal transition, and postnatal morbidity. However, the cardiovascular fetal-to-neonatal adaption is similar between sexes. No study has examined sex differences in newborns during hypoxia, asphyxia, cardio-pulmonary resuscitation, or post-resuscitation recovery. Methods Secondary analysis (two previous publications and two studies currently under peer-review) of 110 term newborn mixed breed piglets (1-3 days of age, weighing 2.0±0.2kg), which were exposed to 30min normocapnic hypoxia followed by asphyxia until asystole, which was achieved by disconnecting the ventilator and clamping the endotracheal tube. This was followed by cardio-pulmonary resuscitation. For the analysis piglets were divided into female and male groups. Cardiac function, carotid blood flow, and cerebral and renal oxygenation were continuously recorded throughout the experiment. Results A total of 35/41 (85%) female and 54/69 (78%) male piglets resuscitated achieved ROSC (p=0.881). The median (IQR) time to achieve return of spontaneous circulation in females and males was 111 (80-228) sec and 106 (80-206)sec (p=0.875), respectively. The 4-hour survival rate was similar between females and males with 28/35 (80%) and 49/54 (91%) piglets surviving (p=0.241), respectively. Conclusions No difference between female and male newborn piglets was observed during hypoxia, asphyxia, resuscitation, and post-resuscitation recovery.